Pengembangan Perilaku Prososial Anak Usia 5-6 Tahun Melalui Permainan Tradisonal Jamuran di RA Al Mabrur - Sumarti; Dian Kristiana; Muhammad ‘Azam Muttaqin (STAI Terpadu Yogyakarta, 2024)
The aim of this study is to find out the implementation of prosocial behavior through the traditional Jamuran game in 5-6 year old children. This study was conducted at RA Al-Mabrur Slogohimo during the odd semester of the academic year 2023/2024. The method used in this work is descriptive qualitative research, the material is collected through interviews, observations and documentation. B class teachers and 5-6 year old children participated in this study. The results of the study show that the Jamuran game can shape prosocial behavior already in early childhood, i.e. children form prosocial behavior related to helping each other by caring for their friends, children's prosocial cooperative behavior by following the rules of the game, prosocial behavior by being honest. friends, the game is about admitting defeat. The steps implemented by the teacher in the game of Jamuran is that the teacher invites the children to gather in the school yard and start the game andquot;Soandquot; player, the player goes around and sings the Jamuran song, and quot;Jadi and quot; player asks a question or order and the losing player takes the